Impact of Uncontrolled HbA1C on The Outcome of Tuberculosis Treatment in TB Patients With Diabetes - Oki Nugraha Putra; Hardiyono Hardiyono; Fitriyatul Rizkiyah; Affan Yuniar N.H (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2020)
Pulmonary tuberculosis (TB) is an infection and communicable disease caused by Mycobacterium tuberculosis. One of the risks to develop active tuberculosis is diabetes mellitus (DM), with two or three times higher than TB patients without DM. Several studies have reported that DM was associated with poor clinical outcomes characterized by a delay of smear sputum conversion or culture conversion in TB patients with DM. However, very limited studies that analyze uncontrolled diabetes by HbA1c level with clinical outcome of TB treatment. This study aims to review the correlation between HbA1c levels and sputum or culture conversion in TB patients with DM. Pubmed, Web of Science, and Embase database were used to search and select the article. We included five studies that met the inclusion criteria. Smear conversion rate at two months was lower in TB patients with DM than those without DM. Uncontrolled HbA1c levels > 6.5%-7.0% were significantly associated with smear conversion of culture conversion for more than two months with a high risk of treatment failure. The positive level of smear sputum at 2-3 months or the end of the intensive phase becomes a strong predictor a failure treatment at the end of the advanced phase. It can be concluded that HbA1c levels delay the smear sputum or culture sputum for more than two months. This review highlights a need for more attention to control HbA1c levels in TB patients with DM to achieve a better outcome.